Real-time 3D plane-wave imaging using annular capacitive micromachined ultrasonic transducer array - Kwon, Young Seok; Kim, Hae Youn; Dong-Hyun Kang; 김동훈; Jeong, Jae-Woong; Lee, Byung Chul (Elsevier BV, 2023)
Imaging methods and 2D sparse arrays have been extensively researched to realize real-time 3D volumetric imaging with higher frame rates. In this study, we developed a 3D plane-wave imaging method using an annular capacitive micromachined ultrasonic transducer (CMUT) array as a breakthrough technique for realizing 3D imaging with a limited number of elements. We adopted the double oxidation and wafer bonding processes for creating the cavity of a CMUT with a 2 ？m silicon membrane. To ensure surface uniformity before the bonding process, we implemented an additional reactive ion etching process after the second oxidation. The characterization results showed that the resonant frequency of the proposed device was 6.2 MHz with 65 V collapse voltage. The demonstration of real-time 3D volumetric imaging was conducted in oil using a Vantage 64 ultrasound research system. A plane-wave imaging scheme was used to detect wire phantoms immersed in the oil, with 289 plane waves transmitted over a range of 20° from the center of the annular array. The reconstructed data were used to create three orthogonal cross sections of the target region. The ？ 6 dB lateral and axial resolutions were 0.56 mm and 0.35 mm for the wires positioned at 18 mm from the proposed device, which were narrow enough to detect a wire phantom of 380 ？m diameter. The normalized frame rate was calculated and compared with that in a previous study. We verified that plane-wave imaging has advantages in real-time imaging when compared with the classic phased array and synthetic phased array. Thus, the annular CMUT array is a promising mechanism for real-time 3D imaging with higher frame rate than that possible with previous methods.